If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2p + 7 = 6(5p + 7) Reorder the terms: 7 + -2p = 6(5p + 7) Reorder the terms: 7 + -2p = 6(7 + 5p) 7 + -2p = (7 * 6 + 5p * 6) 7 + -2p = (42 + 30p) Solving 7 + -2p = 42 + 30p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-30p' to each side of the equation. 7 + -2p + -30p = 42 + 30p + -30p Combine like terms: -2p + -30p = -32p 7 + -32p = 42 + 30p + -30p Combine like terms: 30p + -30p = 0 7 + -32p = 42 + 0 7 + -32p = 42 Add '-7' to each side of the equation. 7 + -7 + -32p = 42 + -7 Combine like terms: 7 + -7 = 0 0 + -32p = 42 + -7 -32p = 42 + -7 Combine like terms: 42 + -7 = 35 -32p = 35 Divide each side by '-32'. p = -1.09375 Simplifying p = -1.09375
| 2x^2-30x-72=0 | | 3x^2=6x+3 | | 7x+40=58-2x | | (2m-1)9+5(5m-3)= | | -33=5x+2 | | 30x^2+32xy-30y^2= | | -5s+15=0 | | 15x^4-64x^3+33x^2= | | 5t-7+31=8(6-4) | | 21x^4-111x^3+30x^2= | | -4m=3 | | 12b^2+3b=0 | | 12y^3+11y^2+2y= | | 1x=17 | | 4y^2+54y-90= | | 15x^2-5x-10= | | 14x^2-53xy+14y^2= | | 5a^2+7ab+2b^2= | | 6x^2+5xy-6y^2= | | -11y=21 | | c=20r+10(40-r) | | 3a^2-8ab-28b^2= | | 4(4x-4)=2(8x+7) | | 12x^2+23xy+5y^2= | | 12x+14x+5=125 | | 6x-15y=105 | | sx+9=x-23 | | (x-10)=6 | | 4*4/3= | | 2(1d+5)=3(1d-2) | | 4/4/3= | | 100x^2-60x-39=0 |